2021
DOI: 10.1111/exd.14295
|View full text |Cite
|
Sign up to set email alerts
|

Substantial alterations of the intestinal microbiota in psoriasis patients of China

Abstract: Substantial alterations of the intestinal microbiota in psoriasis patients of ChinaPsoriasis is an immune-mediated inflammatory skin condition.Accumulating evidence suggests that there is an intimate relationship between intestinal dysbiosis and psoriasis. In order to evaluate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…All studies examined adults, except one study examining both children and adults (age range 10–82 years) ( 11 ) and, in most studies, the psoriatic population was age- and sex-matched with the control population ( 12 23 ). Nine studies included patients with plaque psoriasis only ( 11 13 , 18 , 20 , 23 26 ), 6 studies included patients with mixed psoriasis types ( 15 , 17 , 21 , 22 , 27 , 28 ) and 7 studies did not specify the type of psoriasis ( 14 , 16 , 19 , 29 32 ). Fifteen studies examined patients with mild, moderate or severe psoriasis ( 11 13 , 15 22 , 24 , 25 , 27 , 29 ), 2 studies examined patients with mild psoriasis ( 14 , 32 ) and 4 studies reported no information on psoriasis severity ( 23 , 28 , 30 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies examined adults, except one study examining both children and adults (age range 10–82 years) ( 11 ) and, in most studies, the psoriatic population was age- and sex-matched with the control population ( 12 23 ). Nine studies included patients with plaque psoriasis only ( 11 13 , 18 , 20 , 23 26 ), 6 studies included patients with mixed psoriasis types ( 15 , 17 , 21 , 22 , 27 , 28 ) and 7 studies did not specify the type of psoriasis ( 14 , 16 , 19 , 29 32 ). Fifteen studies examined patients with mild, moderate or severe psoriasis ( 11 13 , 15 22 , 24 , 25 , 27 , 29 ), 2 studies examined patients with mild psoriasis ( 14 , 32 ) and 4 studies reported no information on psoriasis severity ( 23 , 28 , 30 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies included patients with plaque psoriasis only ( 11 13 , 18 , 20 , 23 26 ), 6 studies included patients with mixed psoriasis types ( 15 , 17 , 21 , 22 , 27 , 28 ) and 7 studies did not specify the type of psoriasis ( 14 , 16 , 19 , 29 32 ). Fifteen studies examined patients with mild, moderate or severe psoriasis ( 11 13 , 15 22 , 24 , 25 , 27 , 29 ), 2 studies examined patients with mild psoriasis ( 14 , 32 ) and 4 studies reported no information on psoriasis severity ( 23 , 28 , 30 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that intestinal dysbiosis is closely associated with PSO 34,35 . In a recent study, 36 stool samples were collected from 20 psoriatic patients and 20 healthy controls, and bacterial 16S sequencing was performed to determine how gut microbiota is differed between the two groups. At the genus level, psoriatic group showed a higher abundance of Megamonas and lower abundance of Romboutsia species compared with healthy controls.…”
Section: Disease Aetiologymentioning
confidence: 99%
“…In contrast to psoriasis, 1‐25 atopic dermatitis 26‐47 and pruritus 21,35,48‐70 whose therapeutic landscapes have dramatically changed over the last few years due to many advances in skin research, scleroderma remains a challenge in many aspects.…”
mentioning
confidence: 99%